Kras-mutation influences outcomes for palliative primary tumor resection in advanced colorectal cancer-a Turkish Oncology Group study - (:unkn) unknown (ELSEVIER SCI LTD, 2018)
Purpose: We aimed to investigate the prognostic effect of primary tumor resection (PTR) prior to bevacizumab-based treatments in unresectable metastatic colorectal cancer (mCRC). Methods: We retrospectively collected 341 mCRC cases with unresectable metastases at diagnosis. PTR was performed in 210 cases (the surgery group) and the other patients (n = 131) were followed without PTR (the no-surgery group). All the patients were treated with bevacizumab combined chemotherapy regimens. Results: The median progression free survival (PFS) of the surgery group was 10.4 months (95% CI: 8.9-11.9), which was significantly better than that of the no-surgery group (7.6 months, 95% CI: 6.4-8.8, P = 0.000). The median overall survival (OS) of the surgery group was longer than that of the no-surgery group (27.4 months vs. 18.3 months, respectively, P = 0.000). The median PFS and OS of the surgery group were 10.4 months and 28.2 months, which were significantly longer than that of the no-surgery group in Kras-mutant patients (7.8 months and 18.3 months; P = 0.004, P = 0 .028, respectively). There was no difference in terms of PFS and OS between the surgery and the no-surgery groups in Kras-wild type patients. Conclusion: Palliative PTR may improve the survival outcomes for unresectable mCRC patients. PTR may be preferred, particularly in Kras-mutant patients.
Keywords: Metastatic colorectal cancer; Bevacizumab; Primary tumor resection; UNRESECTABLE SYNCHRONOUS METASTASES; RANDOMIZED PHASE-III; POOLED ANALYSIS; BEVACIZUMAB; CHEMOTHERAPY; COMBINATION; SURVIVAL; EFFICACY; SURGERY; THERAPY